Analysis of the variation of in situ seafloor sediments acoustic characteristics with porosity based EDFM - Zou, Dapeng; Xie, Jin; Meng, Xiangmei; Sun, Han; Feng, Jingchun; Kan, Guangming (Frontiers in Marine Science, 2023)
Numerous factors influence the acoustic characteristics of seafloor sediments, necessitating a comprehensive study that combines theoretical analysis, laboratory measurements and in situ measurements to support acoustic prediction and inversion. In this study, a porosity-based effective density fluid model (P-EDFM) is established to analyze the variation of acoustic properties with the porosity of seafloor sediments. On the biases of P-EDFM, the attribute of measured sound velocity and acoustic attenuation coefficient of seafloor sediment in Series 9B of the SAX99 was well interpreted within the frequency range of 25-100 kHz. The in situ measured sound velocity ratio was well predicated by the P-EDFM in the East China Sea and Yellow Sea. It reveals that the in situ sound velocity ratio decreases with increasing bulk porosity and with decreasing bulk density. The scattering and differences in the acoustic attenuation coefficient measured in situ in seafloor sediments are found to be greater than those observed for sound velocity. After considering the influence of temperature in the P-EDFM, the prediction of in situ sound velocity aligns well with the measured dataset. While, the acoustic attenuation coefficient exhibits an inflection point, increasing initially and then decreasing with changes in porosity, similar to the observed pattern in Hamilton’s observation and estimation. By incorporating temperature and frequency influences, the in situ measurements of sound velocity of seafloor sediments are corrected into laboratory sound velocities by using the P-EDFM. The result reveals the sediment samples’ sampling and transmitting process has a much greater impact on the sound velocity of sandy sediment in the East China Sea compared to muddy sediment. Overall, P-EDFM can predict the in situ sound velocity and sound attenuation coefficient under different temperatures and frequencies, with a lower prediction error for sound velocity compared to sound attenuation coefficient.